A reexamination of long‐duration radial IMF events. Issue 9 (4th September 2014) - Pi, Gilbert; Shue, Jih‐Hong; Chao, Jih‐Kwin; Němeček, Zdenek; Šafránková, Jana; Lin, Chia‐Hsien
Abstract The radial interplanetary magnetic field (IMF) is one of the special solar wind conditions when the orientation of the IMF is aligned with the solar wind velocity. In this study, we reexamine the solar wind condition during the long‐duration radial IMF (>4 h) using the OMNI solar wind data. During the events, the IMF magnitude, solar wind speed, density, and especially its temperature are depressed in comparison with their yearly averages. In contrast to previous studies, we have found that the total time of the radial IMF per year does not change with solar activity. MHD simulation models failed to predict the location of the magnetopause under the radial IMF condition. A part of the inaccuracy is due to the use of assumed solar wind parameters in the simulations. Here we provide MHD modelers with the real solar wind parameters for simulations of the radial IMF.